Determination of Sex by Morphometric Study of Dry Adult Human Sacrum - Naznin, Rawshon Ara; Moniruzzaman, Md; Sumi, Sharmin Akter; Suchi, Halima Akther; Khatun, Mohima; Sultana, Zakia; Foysal, Abdullah Al; Shuaib, Kamruzzaman (Bangladesh Journal of Anatomy, 2017)
Background: Identification of human skeletal remains is a critical problem and is very important in medico legal and anthropological work. Sacrum is one of the last bones to pass away after death and forms an important source of information about sexual dimorphism. The present study was conducted to observe the morphometric measurements of human dry sacrum to establish the possible sex of an individual. Materials and Methods:This study was performed on 60 dried completely ossified, grossly normal adult sacra of unknown sexes fulfilling the inclusion criteria from the stocks of Anatomy laboratory of Sylhet MAG Osmani Medical College, Sylhet from July 2017 to June 2018. Sex determination of the collected unknown sacra was done by using discriminant function analysis and found 30 (50.0%) male and 30 (50.0%) female. By using digital slide calipers and measuring tape different parameters were measured. Results:The length of sacrum was significantly greater in male (107.55 ± 8.89 mm) than female (93.64 ± 6.93 mm) (p<0.001). The breadth of sacrum was significantly greater in female (106.15 ± 5.07 mm) compared to male (101.52 ± 6.81 mm) (p=0.007). The ventral curved length of sacrum was significantly greater in male (113.40 ± 7.91 mm) compared to female (103.87 ± 9.60 mm) (p<0.001). The antero-posterior diameter and transverse diameter of the body of first sacral vertebra did not differ significantly between male and female (p>0.05). The length of the ala of both right and left side did not differ significantly between male and female (p>0.05). The mean antero-posterior diameters of ala of the body of first sacral vertebra of both right and left side did not differ significantly between male and female (p>0.05).The length of sacral auricular surface of right and left side did not differ significantly between male and female (p>0.05).The anterior transverse curvature of pelvic surface of sacrum at the level of S2 and S3 was significantly more in female (81.30 ± 9.60 mm) compared to male (77.47 ± 6.03 mm) (p=0.022). The anterior transverse curvature of pelvic surface of sacrum at the level of S3 and S4 did not differ significantly between male (67.93 ± 7.12 mm) and female (66.40 ± 6.06 mm) (p=0.373). The sacral index was significantly less in male (92.70 ± 5.68 percent) compared to female (111.10 ± 6.85 percent) (p<0.001). The curvature index was significantly more in male (96.07 ± 4.78 percent) compared to female (93.31 ± 5.51 percent) (p=0.007). The index of body of S1 did not differ significantly between male (60.00 ± 6.35 percent) and female (61.81 ± 6.87 percent) (p=0.293). The corporo-basal index did not differ significantly between male (47.75 ± 6.11 percent) and female (45.29 ± 4.04 percent) (p=0.070). The alar index did not differ significantly between male (71.38 ± 10.72 percent) and female (75.73 ± 9.68 percent) (p=0.105). The auricular index was significantly more in male (72.65 ± 7.93 percent) compared to female (67.77 ± 8.73 percent) (p=0.027). Conclusion: The length, curvature index and auricular index of sacrum are greater in male; but the breadth of sacrum, anterior transverse curvature of pelvic surface of sacrum at the level of S2 and S3 and sacral index was greater in female; where as differences of other morphometric parameters are not significant. Bangladesh Journal of Anatomy July 2017, Vol. 15, No. 2 , pp. 48-55